Dealing with Distressed Financial Cooperatives : A Caribbean Experience - Astaphan, Eleanor (World Bank, Washington, DC, 2015)
This working paper analyzes the restructuring of a distressed systemic financial cooperative in the Caribbean and draw lessons for supervisors or policy makers. It explains how the cooperative was intervened, restructured and revived in less than nine months. It analyses how a major contagion impact to the rest of the local financial system was averted with the supervisor building the necessary confidence from the members to recapitalize the cooperative. No public funding was disbursed. Success was never guaranteed during the intervention period and hinged on a comprehensive approach addressing liquidity, solvency and long-term viability issues.